The Rise of Neo-Nationalism in Europe: A Veblenian Perspective. Issue 4 (1st October 2020) - Duroy, Quentin
Abstract: The rise of neo-nationalism has posed a serious threat to European nation-states since the 1990s not only because it is reminiscent of nineteenth and twentieth century ethno-nationalism but also because it reinforces, and is symptomatic of, ongoing social, cultural, and economic tensions in Europe. This article argues that the institutional approach developed by Thorstein Veblen to analyze the role of nationalism during World War I offers meaningful insights to the study of European neo-nationalism today. Veblen's contributions are framed within a critical realist approach in order to provide an analysis of the structural incompatibilities which have been exploited by neo-nationalist parties in Europe. Within this institutional framework, the article offers reflections on neo-nationalism's social, economic, cultural, and political impact upon European democracies.